Inflation and inequality: new evidence from a dynamic panel threshold analysis - Linda Glawe; Helmut Wagner (International Economics and Economic Policy, 2024)
Abstract This paper investigates nonlinearities in the inflation-inequality relationship using a dynamic threshold panel data model and data for 101 countries over the period 1985–2020. We find that inflation rates exceeding 6% are associated with higher income inequality whereas below this threshold, the correlation remains insignificant. From a monetary policy perspective, these findings suggest that a disinflation policy will likely lead to a more equal income distribution in high-inflation countries whereas there is no such effect in a low-inflation setting. In addition, we find that a higher initial level of inequality as well as unemployment has an inequality-enhancing effect. Contrary to previous research, our inflation threshold is endogenously determined, and we control for the Nickell bias arising from the inclusion of the lagged level of inequality. Moreover, our paper covers a much longer time period and also a broader set of developed and developing countries. Our findings have important policy implications, especially against the background of the recent sharp increase in inflation.
Additional information: O11;E31;D31
Keywords: 330; Inflation; Income inequality; Dynamic panel threshold model; Monetary policy; O11; E31; D31